Causes and Risk Factors of Pancreas Graft Loss: A Single Center Study. (July 2018) - Koyama, Ichiro; Nakajima, Ichiro; Iwadoh, Kazuhirok; Sannomiya, Akihito; Muakami, Toru; Nyumura, Izumi; Babazono, Tetsuya; Fuchinoue, Shohei
Background: Outcome after pancreas transplantation has been progressively improving and 1-year graft survival is currently reported to be over 80%. However, Technical failure such as thrombosis and enteric leak is still problematic issue and late pancreas graft loss due to rejection, pancreatitis or recurrence of DM remains a major concern. Although Organ Transplant Act legislated 20 years ago in Japan, organ donation is less than western countries and more than a half of grafts are from marginal donors. The aim of this study was to investigate the cause and risk factors of pancreas graft loss both in early and late phase in our center. Methods: This retrospective cohort study included 63 pancreas transplantation patients between 2001 and 2018 at our institution: SPK; n=55, PAK; n=8. The donor and recipient characteristics, post-operative course, complications were referred to the clinical chart. Univariate and multivariate analyses were performed to evaluate risk factors for pancreas graft loss. Results: Mean donor and recipient age was 38.1± 11.7 and 43.8 ± 7.3 years old respectively. The 1-year, 5-year and 10-year graft survival rate was 88.3%, 78.5% and 68.2%, respectively. Seven patients lost their pancreas graft within 3 months post-operatively. The causes of graft loss were PV thrombosis (n=4) enteric leak (n=3) and infection (n=1). All 4 thrombosis episodes occurred in PAK recipients and 3 pancreas grafts were transplanted into left iliac fossa. Meanwhile 5 patients lost pancreas graft more than 2 years after the transplant due to chronic rejection (n=3), recurrence of type 1 DM (n=2) and pancreatitis (n=1). Using the Kaplan-Meier method, the pancreas graft survival was better in SPK than in PAK transplants (Log Rank test: P = 0.0206). Multivariate analysis showed that pancreas graft loss was influenced by donor age (P = .0043) and PAK (P = .022). Conclusions: Appropriate donor selection is essential to overcome perioperative complications. For long-term survival, closer observation and immunological assessment including DSA and auto-Ab measurement are necessary.